2019
DOI: 10.1177/0192636519853029
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Perceptions of Transformed School Counselors

Abstract: This study investigated the relationship between the Transformed School Counseling (TSC) initiative counselor educator programs, the perceptions of school principals hiring TSC-prepared school counselors, and factors affecting principal’s hiring practices. Results indicated that principal’s value TSC candidates because they: (a) have effective principal-counselor relationships that positively affect students, (b) exemplify leadership qualities, (c) align their work with the mission of the school, (d) have stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…When school counselors collaborate with administrators, they can leverage the relationships to positively affect students and support schools' missions, resulting in higher job satisfaction and lower turnover rates (Clemens et al, 2009;Lawrence & Stone, 2019). Administrators can play an essential role in supporting school counselors' wellness and ability to support students effectively.…”
mentioning
confidence: 99%
“…When school counselors collaborate with administrators, they can leverage the relationships to positively affect students and support schools' missions, resulting in higher job satisfaction and lower turnover rates (Clemens et al, 2009;Lawrence & Stone, 2019). Administrators can play an essential role in supporting school counselors' wellness and ability to support students effectively.…”
mentioning
confidence: 99%
“…The behavior of the principal who supports the guidance and counseling activities and wants to work with the counselor and hear input from the counselor will improve the performance of the counselor. The results of school leadership or consultative willingness to communicate with counselors are types of leadership that contribute to counselor performance and their good achievement (Dahir et al, 2011;Lawrence & Stone, 2019;Shillingford & Lambie, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A substantial body of research, mostly conducted in the U.S., has found that principals’ perceptions of school counselling are not consistent with the role descriptions found in counselling models such as the ASCA National Model (Kirchner & Setchfield, 2005; Lawrence & Stone, 2019; Perusse et al, 2004). In the Philippines, David (2017) identified a lack of principals’ understanding of counsellors’ work, principals assigning inappropriate tasks to counsellors, and principals having unrealistic expectations of counsellors, as impediments to effective counselling.…”
Section: Discussionmentioning
confidence: 99%